The Role of Phenolic Compounds in Antioxidant Enhancement in Obese Individuals: A Systematic Literature Review - Maulani, Sifa; Farapti, Farapti (Universitas Airlangga, 2025)
Background: Chronic inflammation and oxidative stress are complications of obesity. Consuming phenolic compounds found in plant-based foods can reduce inflammation and oxidative stress. Phenolic compounds are phytochemicals with antioxidant properties that play an important role in health. Objectives: This article aims to examine the role of phenolic compounds in obese individuals. Methods: This article uses a literature review method with predetermined inclusion and exclusion criteria. Articles were searched for in several electronic databases, namely PubMed and Wiley Online Library. Results: Phenolic compounds can reduce inflammation and oxidative stress through several mechanisms. One of these is that fermented flaxseed extract improves neural health and reduces obesity markers in experimental models. Polyphenolic compounds from pigmented rice effectively reduced lipid peroxidation and pro-inflammatory cytokines. The findings highlight the anti-adipogenic, anti-inflammatory, and metabolic regulation properties of phenolic compounds. Conclusion: Phenolic compounds play an important role in reducing oxidative stress and inflammation in obesity. Their effectiveness varies depending on the source of the compounds, with promising results from pigmented rice, fermented black beans, and fermented flaxseed. However, most results are from in vitro or animal studies, so further clinical trials are needed to validate these benefits in humans.